2017
DOI: 10.4102/jsava.v88i0.1466
|View full text |Cite
|
Sign up to set email alerts
|

Tremors in white rhinoceroses (<i>Ceratotherium simum</i>) during etorphine–azaperone immobilisation

Abstract: Little is known about the mechanisms causing tremors during immobilisation of rhinoceros and whether cardiorespiratory supportive interventions alter their intensity. Therefore, we set out to determine the possible mechanisms that lead to muscle tremors and ascertain whether cardiorespiratory supportive interventions affect tremor intensity. We studied tremors and physiological responses during etorphine–azaperone immobilisation in eight boma-held and 14 free-living white rhinoceroses. Repeated measures analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…The addition of azaperone to etorphine in the dart, allows a reduction in blood pressure and reduces muscle tremors which further reduces blood oxygen levels, while intravenous administration of butorphanol in recumbent animals causes the heart to slow down to normal values, most likely due to reduce the hypoxemia [40]. The study conducted in two groups of rhinoceroses, free-ranging and boma-held individuals, confirmed the effect of intravenously administered butorphanol on decreasing the muscle tremor intensity in both groups of animals [41].…”
Section: The Use Of Veterinary Medicinal Productssupporting
confidence: 53%
“…The addition of azaperone to etorphine in the dart, allows a reduction in blood pressure and reduces muscle tremors which further reduces blood oxygen levels, while intravenous administration of butorphanol in recumbent animals causes the heart to slow down to normal values, most likely due to reduce the hypoxemia [40]. The study conducted in two groups of rhinoceroses, free-ranging and boma-held individuals, confirmed the effect of intravenously administered butorphanol on decreasing the muscle tremor intensity in both groups of animals [41].…”
Section: The Use Of Veterinary Medicinal Productssupporting
confidence: 53%
“…Acidosis, hypercapnia and a low arterial partial pressure of oxygen (PaO 2 ) are common in opioid-immobilised white rhinoceroses, indicating marked cardiorespiratory depression [1,46]. Our findings help to explain why despite the seemingly extremely low SaO 2 values reported in these animals, recovery is usually uneventful, without obvious clinical signs of long-term damage associated with such severe hypoxaemia.…”
Section: Discussionmentioning
confidence: 71%
“…Severe side effects (e.g. muscle tremors, tachycardia, hypertension, hypercapnia, low partial pressure of oxygen (pO 2 ) and acidosis) occur regularly and are well described [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rhinoceroses immobilized with etorphine based drugcombinations are known to exhibit severe tachycardia and systemic hypertension resulting from the effects of the potent opioid combined with sympathetic activation (48,49). Elevated plasma epinephrine concentrations at TC compared to the other sample time points indicated that our rhinoceroses likely experienced tachycardia and hypertension, which for logistical reasons, we were not able to measure.…”
Section: Hematological Responsementioning
confidence: 96%